Polyolefin material with intrinsic antioxidant properties and method for its preparation and use
Patent Information
- Application Number
- CN202610763931.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-13
AI Technical Summary
然而,由于绝大多数抗氧化剂为极性分子,与非极性的聚烯烃基体相容性较差,导致抗氧化剂分散不均、迁移析出问题严重,使得材料的长期氧化稳定性大打折扣
[0008]基于上述技术方案,本发明的具有本征抗氧化性能的聚烯烃材料及其制备方法和应用至少存在以下有益效果之一:
Smart Images

Figure CN122897937A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of olefin polymerization technology, and particularly relates to a polyolefin material with intrinsic antioxidant properties and its preparation method, radiation crosslinked polyolefin material, polyolefin fiber, and its application. Background Technology
[0002] Polyolefins (such as polyethylene and polypropylene) are the most widely produced and used synthetic polymer materials. During long-term use or high-temperature processing, polyolefins inevitably undergo thermo-oxidative degradation, thus requiring the addition of antioxidants to extend their service life. Currently, the common industrial method is to introduce antioxidants into the polyolefin matrix through physical mixing during post-polymerization granulation or processing. However, since most antioxidants are polar molecules, they have poor compatibility with the non-polar polyolefin matrix, leading to uneven dispersion and severe migration and precipitation problems, significantly reducing the long-term oxidative stability of the material. Summary of the Invention
[0003] To address the aforementioned technical problems, this invention provides a polyolefin material with intrinsic antioxidant properties, its preparation method, and its application, aiming to at least partially solve the above-mentioned technical problems. The technical solution provided by this invention is as follows.
[0004] As a first aspect of the present invention, a method for preparing a polyolefin material with intrinsic antioxidant properties is provided, comprising: in a polymerization solvent, using a bifunctional catalyst to catalyze the polymerization reaction of at least one olefin monomer to obtain a polyolefin material with intrinsic antioxidant properties; wherein the bifunctional catalyst is a transition metal complex containing phenolic hydroxyl groups, the phenolic hydroxyl groups being located on the backbone or side chain of a ligand coordinated to the center of the transition metal, or directly coordinated to the center of the transition metal.
[0005] As a second aspect of the present invention, a polyolefin material prepared by the above preparation method is provided, wherein the residual amount of the bifunctional catalyst in the polyolefin material is 0.005wt%-0.5wt%.
[0006] As a third aspect of the present invention, a polyolefin material article is provided, the polyolefin material article comprising radiation-crosslinked polyolefin material or polyolefin fiber; wherein the radiation-crosslinked polyolefin material is obtained by radiation crosslinking treatment of the above-mentioned polyolefin material; the polyolefin fiber is obtained by gel spinning and multi-stage thermal stretching of the above-mentioned polyolefin material.
[0007] As a fourth aspect of the present invention, the application of polyolefin materials, radiation-crosslinked polyolefin materials, or polyolefin fibers in textiles and medical devices is provided.
[0008] Based on the above technical solution, the polyolefin material with intrinsic antioxidant properties of the present invention, its preparation method, and its application have at least one of the following beneficial effects:
[0009] (1) In this invention, the bifunctional catalyst has both catalytic and antioxidant functions for olefin polymerization. It directly imparts antioxidant capacity to the resulting polyolefin material during the catalytic polymerization process, without the need to add antioxidants after polymerization.
[0010] (2) In this invention, the polyolefin material prepared by the preparation method provided by this invention can exhibit excellent antioxidant properties and good mechanical properties with a low content of bifunctional catalyst (i.e., antioxidant structure).
[0011] (3) In this invention, polyolefin materials with higher mechanical properties can be obtained by using the polyolefin materials of this invention through processes such as irradiation crosslinking or gel spinning. Depending on the different mechanical properties of polyolefin materials, irradiated crosslinked polyolefin materials, and polyolefin fibers, they can be applied to fields such as textiles and medical devices. Attached Figure Description
[0012] Figure 1 This is a schematic diagram illustrating the mechanism by which the present invention prepares polyolefin materials with intrinsic antioxidant properties.
[0013] Figure 2 This is a graph showing the oxidation induction time of different samples in Example 1 of the present invention;
[0014] Figure 3 This is a diagram showing the initial oxidation temperatures of different samples in Example 1 of the present invention;
[0015] Figure 4 The NMR spectrum of the polymer PE-Ni4 sample in Example 2 of this invention;
[0016] Figure 5 This is the NMR spectrum of the polymer PE-Ni4-OH sample in Example 2 of the present invention;
[0017] Figure 6 This is a graph showing the oxidation induction time of different samples in Example 2 of the present invention;
[0018] Figure 7 This is a comparison chart of oxidation induction time for samples prepared by introducing auxiliary antioxidants in Example 4 of the present invention;
[0019] Figure 8 This is a diagram showing the initial oxidation temperature of the sample prepared by introducing an auxiliary antioxidant in Example 4 of the present invention;
[0020] Figure 9 This is a comparison chart of oxidation induction time for samples prepared by introducing a natural antioxidant carrier in Example 5 of the present invention;
[0021] Figure 10 This is a diagram showing the initial oxidation temperature of the sample prepared by introducing a natural antioxidant carrier in Example 5 of the present invention.
[0022] Figure 11 These are the electron spin resonance (ESR) spectra of different samples after radiation crosslinking in Example 6 of this invention;
[0023] Figure 12 This is a graph showing the oxidation induction time of different samples before and after radiation crosslinking in Example 6 of the present invention;
[0024] Figure 13 The graphs show the creep resistance of different samples before and after radiation crosslinking in Example 6 of this invention.
[0025] Figure 14 The mechanical properties of different fiber samples in Example 7 of this invention are shown in the diagram.
[0026] Figure 15 The graphs show the mechanical properties of different fiber samples after different aging times in Example 7 of this invention. Detailed Implementation
[0027] Currently, the physical mixing method for introducing antioxidants into polyolefin matrices suffers from poor compatibility, resulting in uneven distribution and severe migration and precipitation problems, significantly reducing the antioxidant properties of the resulting materials. To address these issues, several chemical modification methods have been proposed, such as synthesizing polymeric antioxidants, covalently grafting antioxidants onto polyolefin chains, or introducing antioxidant functional groups through coordination copolymerization. While these methods improve the dispersibility and anti-migration properties of antioxidants to some extent, they generally suffer from drawbacks such as complex synthesis processes, high costs, and poor versatility. This is particularly true for ultra-high molecular weight polyethylene (UHMWPE), whose extremely high molecular weight (tens of thousands to millions) and chain entanglement make melt processing very difficult, and the lack of reactive sites on the molecular chains makes the aforementioned chemical modification methods difficult to implement effectively. Furthermore, in practical applications, UHMWPE typically requires processing under harsh conditions such as high-temperature compression molding and radiation crosslinking, placing even stricter requirements on the stability of antioxidants.
[0028] In response, this application proposes a catalyst that has both catalytic and antioxidant functions, and applies it to the olefin polymerization process, so that the prepared polyolefin material has intrinsic antioxidant properties and excellent mechanical properties.
[0029] The term "polyolefin material with intrinsic antioxidant properties" in this invention refers to a polyolefin material with antioxidant properties that is directly obtained through olefin polymerization without the introduction of external antioxidants.
[0030] In this invention, the term "phenolic hydroxyl" refers to a hydroxyl group (-OH) directly attached to an aromatic ring, which may be located on the main skeleton or side chain of the ligand.
[0031] The term "substitution" in this invention refers to the substitution of one or more hydrogen atoms in a molecule by one or more non-hydrogen atoms. The term "substituent" as used herein refers to a group that can be substituted or replaced onto a molecule. Substituents include, but are not limited to, halogens, hydroxyl groups, alkoxy groups, aryloxy groups, aralkyloxy groups, oxo (carbonyl) groups, carboxyl groups, sulfur-containing groups, and nitrogen-containing groups.
[0032] Halogens are selected from F, Cl, Br, and I; carboxyl groups are selected from carboxylic acids, carboxyl salts, and carboxylic esters; oxygen-containing groups can be alkoxy, aryloxy, aralkyloxy, or oxygen (carbonyl); sulfur-containing groups are selected from mercapto, alkylthio, arylthio, sulfoxide, sulfonyl, sulfonyl, and sulfonamide; nitrogen-containing groups are selected from amino, hydroxyamino, nitrile, nitro, nitrogen oxides, acylhydrazine, azide, and enamine.
[0033] The term "weight-average molecular weight" in this invention refers to M. w It is equal to ΣM i 2n i / ΣM i n i , where n i It is the molecular weight M i The number of molecules and the weight-average molecular weight can be determined using gel permeation chromatography.
[0034] The term "air" in this invention refers to a mixture of gases whose composition is approximately equivalent to the natural composition of gases obtained from the atmosphere, typically at ground level. In some instances, air is obtained from the surrounding environment. The components of air include approximately 78% nitrogen, 21% oxygen, 1% argon, and 0.04% carbon dioxide, as well as trace amounts of other gases.
[0035] In this invention, the term "room temperature" refers to approximately 15°C to 28°C.
[0036] Specifically, the present invention provides a method for preparing a polyolefin material with intrinsic antioxidant properties, comprising: in a polymerization solvent, using a bifunctional catalyst to catalyze the polymerization reaction of at least one olefin monomer to obtain a polyolefin material with intrinsic antioxidant properties; wherein, the bifunctional catalyst is a transition metal complex containing phenolic hydroxyl groups, the phenolic hydroxyl groups being located on the backbone or side chain of a ligand coordinated with the center of the transition metal, or directly coordinated with the center of the transition metal.
[0037] In the preparation method of this invention, the bifunctional catalyst is a transition metal complex containing phenolic hydroxyl groups, possessing both catalytic and antioxidant functions for olefin polymerization. While catalyzing the polymerization reaction of olefins, it directly imparts antioxidant capacity to the resulting polyolefin material by utilizing the hydrogen atom transfer or free radical scavenging ability of the contained phenolic hydroxyl groups, eliminating the need for post-polymerization antioxidant addition. This preparation method is widely applicable, simple, and produces polyolefin materials with low residual levels of bifunctional additives, exhibiting excellent mechanical and antioxidant properties.
[0038] According to embodiments of the present invention, the bifunctional catalyst is a transition metal complex containing a phenolic hydroxyl group. This can be understood as comprising at least one phenolic hydroxyl group, a transition metal center, and a ligand coordinated to the transition metal center. The phenolic hydroxyl group is located on the backbone or side chain of the ligand coordinated to the transition metal center, or is directly coordinated to the transition metal center. The ortho and / or para positions of the phenolic hydroxyl group can be substituted by at least one substituent selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, hydroxyl, alkoxy, aryloxy, aralkyloxy, oxo (carbonyl), carboxyl, carboxylate, carboxylate ester, mercapto, alkylthio, arylthio, sulfoxide, sulfonyl, sulfonamide, amino, hydroxyamino, nitrile, nitro, cyano, acylhydrazine, azide, and enamine, more preferably methyl, ethyl, or isopropyl, to form a hindered phenolic structure.
[0039] Specifically, the transition metal is selected from any one of Group IVB, Group VB, Group VIB, Group VIIB, Group VIII, Group IB, or Group IIB metals. Preferably, the transition metal is selected from at least one of titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), chromium (Cr), iron (Fe), cobalt (Co), nickel (Ni), and palladium (Pd); more preferably, it is nickel (Ni), iron (Fe), or titanium (Ti).
[0040] The ligand is selected from any one of phosphonophenol ligands, α-diimine ligands, pyridine-imine ligands, pyridine-bisimine ligands, and bis(phenoxy-imine) ligands. Therefore, the bifunctional catalyst of the present invention includes any one of the following: phosphonophenol type, α-diimine ligand type, pyridine-imine ligand type, pyridine-bisimine ligand type, and bis(phenoxy-imine) ligand type bifunctional catalysts. When the bifunctional catalyst is an α-diimine ligand type, pyridine-imine ligand type, pyridine-bisimine ligand type, or bis(phenoxy-imine) ligand type bifunctional catalyst, a co-catalyst is also added during the polymerization reaction. The co-catalyst is selected from any one of alkylaluminoxanes, alkylaluminum, phenylaluminum, and alkylaluminum chloride.
[0041] The general structure of the phosphonol ligand-type bifunctional catalyst is shown in formula (1) below, where P is a phosphorus-containing group (such as phosphine, hypophosphite, phosphonate, etc.), and O is a phenolic oxygen anion or phenolic hydroxyl group. The two form a five-membered chelate ring with the transition metal M through an ortho-substituted aromatic ring.
[0042] Equation (1);
[0043] Among them, R1, R2, and R3 are each independently selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl groups, where Ar1 and Ar2 are each independently selected from substituted or unsubstituted C6-C groups. 20 Aryl or C4-C 20 Heteroaryl groups, in which the heteroatom can be any one of N, S, or O, and the substituents are selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydroxyl, and carboxyl groups; M is a transition metal, preferably Ni. More preferably, R1 is tert-butyl, R2 is H or OH, or R1, R2, and R3 are all tert-butyl.
[0044] In some embodiments, the structure of the phosphonophenol ligand-type bifunctional catalyst is shown in formula (1-1):
[0045] Equation (1-1);
[0046] Among them, R1, R2, and R3 are each independently selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl, where M is a transition metal, preferably Ni.
[0047] The general structure of the α-diimine ligand-type bifunctional catalyst is shown in formula (2) below, wherein two imine nitrogen atoms coordinate with the transition metal M to form a five-membered chelate ring, and at least one phenolic hydroxyl group is attached to the aryl substituent of the α-diimine ligand.
[0048] Equation (2);
[0049] Among them, R1 is selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl, where Ar1 is selected from substituted or unsubstituted C6-C.20 Aryl, substituted or ortho-substituted C4-C 20 Heteroaryl and phenolic hydroxyl groups, wherein the heteroatom in the heteroaryl group can be any one of N, S, or O, and the substituents are selected from C1-C2. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydroxyl, and carboxyl groups; M is a transition metal, preferably Ni or Pd; X1 and X2 may be the same or different, and are each independently selected from Br or Cl.
[0050] The pyridine-imine ligand type bifunctional catalyst is formed by the coordination of a pyridine single atom and an imine unit with a transition metal M to form a five-membered chelate ring, and its general formula structure is shown in the following formula (3):
[0051] Equation (3);
[0052] Among them, R1 is selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl groups, where Ar1 and Ar2 are each independently selected from substituted or unsubstituted C6-C groups. 20 Aryl or C4-C 20 Heteroaryl groups, in which the heteroatom can be any one of N, S, or O, and the substituents are selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydroxyl, and carboxyl groups; M is a transition metal, preferably Ni; X1 and X2 may be the same or different, and are each independently selected from Br and Cl.
[0053] In some embodiments, the structure of the pyridine-imine ligand-type bifunctional catalyst is shown in formula (3-1):
[0054] Equation (3-1);
[0055] Among them, R1 is selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl; M is a transition metal, preferably Ni; X1 and X2 may be the same or different, and are each independently selected from Br and Cl.
[0056] The pyridine-bisimine ligand-type bifunctional catalyst is a tripentate chelate structure formed by the coordination of a pyridine nitrogen atom and two imine nitrogen atoms with a transition metal M. At least one phenolic hydroxyl group is attached to the aryl substituent of the pyridine-bisimine ligand. The general formula of the pyridine-bisimine ligand-type bifunctional catalyst is shown in formula (4):
[0057] Equation (4);
[0058] Ar1 and Ar2 are each independently selected from substituted or unsubstituted C6-C. 20 Aryl or C4-C 20 Heteroaryl groups, in which the heteroatom can be any one of N, S, or O, and the substituents are selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydroxyl, and carboxyl groups; M is a transition metal, preferably Fe; X1 and X2 may be the same or different, and are each independently selected from Br and Cl.
[0059] In some embodiments, the structural formula of the pyridine-bisimine type ligand bifunctional catalyst is shown in formula (4-1):
[0060] Equation (4-1);
[0061] Among them, R1 and R2 are each independently selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl; M is a transition metal, preferably Fe; X1 and X2 may be the same or different, and are each independently selected from Br and Cl.
[0062] The bifunctional catalyst with bis(phenoxy-imine) ligands has two [O,N] bidentate units that are coordinated to the same transition metal M. Each [O,N] unit is composed of a phenoxy anion / phenolic hydroxyl group (O) and an imine nitrogen atom (N), and the aryl group on the ligand skeleton is further connected to a phenolic hydroxyl group. The specific general formula structure is shown in formula (5).
[0063] Equation (5);
[0064] Among them, R1, R2, and R3 are each independently selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl, M is a transition metal, preferably Ti; X1 and X2 may be the same or different, and are each independently selected from Br and Cl.
[0065] In some embodiments, the structure of the bis(phenoxy-imine) ligand-type bifunctional catalyst is shown in formula (5-1):
[0066] Equation (5-1);
[0067] Among them, R1, R2, and R3 are each independently selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl; M is a transition metal, preferably Ti; X1 and X2 may be the same or different, and are each independently selected from Br and Cl.
[0068] According to an embodiment of the present invention, the polymerization reaction is carried out in a polymerization solvent, wherein the polymerization solvent is selected from alkane solvents or benzene homologue solvents, such as any one of hexaane, n-heptane, cyclohexane, and toluene; the polymerization reaction is carried out in the form of precipitation polymerization, so that the bifunctional catalyst is embedded in situ into the interior of the polyolefin material to achieve uniform dispersion.
[0069] Figure 1 This is a schematic diagram illustrating the mechanism by which the present invention prepares polyolefin materials with intrinsic antioxidant properties.
[0070] like Figure 1 As shown, the transition metal center and ligand are linked to form a bifunctional catalyst with catalytic and antioxidant functions. It can catalyze the precipitation polymerization reaction of olefin monomers (such as ethylene) to obtain polyolefin materials. The bifunctional catalyst is embedded in situ into the interior of the polyolefin material and is uniformly dispersed.
[0071] According to embodiments of the present invention, a method for preparing a polyolefin material with intrinsic antioxidant properties further includes: adding an auxiliary antioxidant to generate a synergistic antioxidant effect with the bifunctional catalyst. This can be understood as follows: in the polymerization solvent, the bifunctional catalyst acts as a catalyst on one hand, and together with the auxiliary antioxidant, it acts as an antioxidant component, imparting excellent antioxidant properties to the polyolefin material. In some embodiments, the auxiliary antioxidant is selected from at least one of butylated hydroxytoluene (BHT) and tert-butylhydroquinone (TBHQ), and the amount of the auxiliary antioxidant is 0.1-10 times the molar amount of the bifunctional catalyst.
[0072] According to embodiments of the present invention, a method for preparing a polyolefin material with intrinsic antioxidant properties further includes: loading a bifunctional catalyst onto a natural antioxidant support, and forming a heterogeneous catalyst catalyzing at least one olefin monomer to undergo a polymerization reaction to prepare a polyolefin material with intrinsic antioxidant properties. The natural antioxidant support is a compound containing phenolic hydroxyl groups, selected from at least one of lignin, leucine, epigallocatechin gallate (EGCG), tannic acid, carotenoids, terpenoids, and vitamins, so as to utilize the phenolic hydroxyl groups in the natural antioxidant support and the phenolic hydroxyl groups in the bifunctional catalyst to jointly impart antioxidant capacity to the polyolefin material. The bifunctional catalyst of the present invention can be loaded onto a natural antioxidant support containing phenolic hydroxyl groups via phenolic hydroxyl groups or anchoring groups on ligands (the anchoring groups being metal salts (-ONa, -OK, -OLi) formed by hydroxyl groups and metal hydrides (such as NaH, KH, LiH)).
[0073] As a second aspect of the present invention, a polyolefin material prepared by the above preparation method is provided, wherein the residual amount of the bifunctional catalyst in the polyolefin material is 0.005wt%-0.5wt%.
[0074] In this invention, the polyolefin material prepared by the preparation method provided by this invention can exhibit excellent antioxidant properties and good mechanical properties with a low residual amount of antioxidant structure (i.e., the residual amount of bifunctional catalyst is 0.005wt%-0.5wt%).
[0075] According to embodiments of the present invention, the polyolefin material prepared by the above-described preparation method can be selected from at least one of branched polyethylene, polyethylene wax, bimodal polyethylene, and ultra-high molecular weight polyethylene (UHMWPE). Wherein, when the polyolefin material is ultra-high molecular weight polyethylene, the weight-average molecular weight is greater than 1 × 10⁻⁶. 6 The tensile strength is 40MPa-70MPa, and the elongation at break is 150%-600%. Furthermore, the polyolefin material prepared by the above method has a residual content of 0.015wt% of the bifunctional catalyst, or even less than 0.005wt%. However, the resulting polyolefin material exhibits an oxidation induction time of several minutes to tens of minutes at 200℃ in a pure oxygen atmosphere, and its initial oxidation temperature (Td0) is more than 50℃ higher than that of polyolefin without antioxidants. Simultaneously, the tensile strength, elongation at break, yield strength, and other mechanical properties of the polyolefin material remain good, meeting processing and usage requirements.
[0076] In some implementations, the oxidation induction time is at least 5 min, at least 10 min, at least 20 min, at least 45 min, and at most 5 min. If it exceeds 60 min, the temperature needs to be increased for testing.
[0077] In some embodiments, the polyolefin material prepared by the method provided by the present invention can achieve an oxidation induction time of 5-60 min at 200°C in a pure oxygen atmosphere.
[0078] As a third aspect of the invention, a polyolefin material article is provided, comprising radiation-crosslinked polyolefin material or polyolefin fiber.
[0079] In some embodiments, the radiation-crosslinked polyolefin material is obtained by irradiating and crosslinking the aforementioned polyolefin material.
[0080] In this invention, the polyolefin material prepared by the above preparation method is subjected to irradiation treatment. Because the antioxidant component (i.e., bifunctional catalyst) in the polyolefin material is uniformly distributed, it can effectively quench the residual free radicals generated by irradiation. After crosslinking, it can still effectively maintain excellent antioxidant properties and mechanical properties (such as toughness). It can be applied to medical devices, such as artificial joints and other medical implants.
[0081] According to embodiments of the present invention, the irradiation crosslinking is performed using gamma rays or electron beams, with a total dose of 10kGy to 200kGy, for example, 10kGy, 20kGy, 50kGy, 80kGy, 100kGy, 150kGy, or 200kGy.
[0082] In some embodiments, the polyolefin fiber is obtained from the above-mentioned polyolefin material by gel spinning and multi-stage thermal stretching.
[0083] In this invention, the fibers obtained by gel spinning exhibit significantly better strength retention in long-term thermal aging experiments than the comparative fibers with added traditional antioxidants.
[0084] Specifically, the polyolefin material is added to white oil, cooled, and then extruded through a 0.5mm spinneret at 100-150°C. After being extracted multiple times with dichloromethane and dried, it is subjected to multi-stage hot stretching at 80-100°C, wherein the stretching ratio is 1.5-10, for example, 1.5, 2, 5, 10, preferably 5-10.
[0085] According to an embodiment of the present invention, the tensile strength of the polyolefin fiber monofilament is ≥40 cN / dtex, and the initial modulus is ≥1000 cN / dtex.
[0086] As a fourth aspect of the present invention, the application of polyolefin materials, radiation-crosslinked polyolefin materials, and polyolefin fibers in textiles and medical devices is provided.
[0087] In this invention, polyolefin materials with higher mechanical properties can be obtained by using processes such as irradiation crosslinking or gel spinning. Depending on the different mechanical properties of the polyolefin materials, irradiated crosslinked polyolefin materials, and polyolefin fibers, they can be applied to fields such as textiles and medical devices.
[0088] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the invention. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the invention for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.
[0089] catalyst
[0090] 1. Phosphine nickel catalyst
[0091] 1) The structural features of catalyst Ni1 are: 2',6'-dimethoxy-[1,1'-biphenyl]-2-yl is attached to P, and a phenolic hydroxyl group (-OH) is present in the ortho position of the aromatic ring containing the phenolic oxygen.
[0092] 2) The structural features of catalyst Ni2 are: based on Ni1, the para position of the aromatic ring containing phenolic oxygen contains a second phenolic hydroxyl group, which enables a single ligand to provide dual antioxidant sites.
[0093] 3) The structural features of catalyst Ni3 are as follows: Based on Ni1, the ortho and para positions of the aromatic ring containing phenolic oxygen are replaced by tert-butyl groups to form a hindered phenolic structure (2,6-di-tert-butylphenol analog), thereby significantly enhancing antioxidant activity.
[0094] 2. α-Diimine Nickel Catalyst
[0095] 1) The Ni4 catalyst adopts an α-diimine ligand structure, where R is methyl (Me) and the transition metal is Ni.
[0096] 2) The Ni4-OH catalyst adopts an α-diimine ligand structure, in which R is a hydroxyl group (OH) and the transition metal is Ni.
[0097] 3. Pyridine-imine type catalyst
[0098] The aryl substituent of the pyridine-imine ligand is hydroxyl, and the transition metal is Ni.
[0099] 4. Pyridine-bisimine type catalyst
[0100] The aryl substituent of the pyridine-bisimine ligand is hydroxyl, and the transition metal is Fe.
[0101] 5. Titanium-based catalysts
[0102] The aryl substituent of the bis(phenoxy-imine) ligand is hydroxyl, and the transition metal is Ti.
[0103] The specific structures of the above-mentioned phosphonophenol nickel catalyst, α-diimine nickel catalyst, pyridine-imine catalyst, pyridine-bisimine catalyst, and titanium system catalyst are shown below:
[0104] .
[0105] Example 1: Basic Aggregation Method
[0106] A 350 mL glass pressure reactor was pre-dried at 130 °C for at least 1 h and then adjusted to room temperature. 18 mL of n-heptane was added under nitrogen atmosphere. Subsequently, 0.5 μmol of phosphonophenol ligand and an equimolar amount of Ni(COD)₂ were added to 2 mL of n-heptane and stirred for 1 min. This mixture was then injected into the reactor using a syringe to form catalysts Ni₁, Ni₂, and Ni₃. Ethylene was introduced and maintained at 8 bar with rapid stirring. After reacting for 15 min, the atmosphere was vented and 100 mL of ethanol was added to terminate the reaction, thus obtaining ultra-high molecular weight polyethylene (UHMWPE), abbreviated as PE-Ni₁, PE-Ni₂, and PE-Ni₃, respectively.
[0107] Post-polymerization treatment: The resulting polymer was washed with ethanol and filtered to remove the bifunctional catalyst used in the reaction, and then dried under vacuum at 50°C to constant weight. It should be noted that no additional purification steps, such as dissolution-precipitation or Soxhlet extraction, were performed to ensure that the bifunctional catalyst residues (including antioxidant functionalized ligands) remained within the polymer matrix for subsequent characterization.
[0108] Example 2: Polymerization methods using other catalytic systems
[0109] Polyolefin materials were prepared using the same method as in Example 1, except that the phosphonophenol ligands (Ni1, Ni2, Ni3) and equimolar Ni(COD)2 formed a phosphonophenol nickel catalyst, which was replaced with: α-diimine nickel catalyst Ni4 and α-diimine nickel catalyst Ni4-OH for the synthesis of branched polyethylene; pyridine-imine nickel catalyst Ni5 and pyridine-imine nickel catalyst Ni5-OH for the synthesis of polyethylene wax; and bis(phenoxy-imine)titanium catalyst Ti and bis(phenoxy-imine)titanium catalyst Ti-OH for the synthesis of ultra-high molecular weight polyethylene (UHMWPE). The amount of the aforementioned catalysts was 1 μmol, and 500 equivalents of Et2AlCl (2M n-heptane solution) were added as a co-catalyst.
[0110] For both the pyridine-bisimine iron catalyst Fe and the pyridine-bisimine iron catalyst Fe-OH, the catalyst dosage was 1 μmol, and 500 equivalents of Et3Al were added as a co-catalyst to synthesize bimodal polyethylene with intrinsic antioxidant properties.
[0111] The resulting polymers were named PE-Ni4, PE-Ni4-OH, PE-Ni5, PE-Ni5-OH, PE-Fe, PE-Fe-OH, PE-Ti, and PE-Ti-OH, respectively.
[0112] Post-polymerization treatment: After quenching the polymerization reaction with acidified ethanol, the resulting polymer slurry was poured into a large volume of ethanol. The solid product was then repeatedly washed with fresh ethanol to remove residual co-catalyst and unreacted catalyst components. Finally, the polymer was collected by filtration and vacuum dried to constant weight at 50°C. It is particularly noteworthy that no additional purification steps, such as dissolution-reprecipitation or Soxhlet extraction, were performed. This ensured that catalyst residues (including antioxidant functionalized ligands) remained in the polymer matrix for subsequent characterization.
[0113] Example 3: High-pressure polymerization method
[0114] Polyolefin materials were prepared using the same method as in Example 1, except that the ethylene pressure was increased to 30 atm, the reaction time was extended to 30 min, the amount of n-heptane used was 100 mL, and the bifunctional catalyst was Ni1 at a dosage of 0.5 μmol. This was used to evaluate the performance of the bifunctional catalyst under near-industrial conditions. Under these conditions, the catalyst polymerization activity reached 198 kg PE / g Ni.
[0115] Example 4: Strategies for Enhancing the Role of Assisted Antioxidants
[0116] Polyolefin materials were prepared using the same method as in Example 1, except that: 0.5 μmol of BHT (dissolved in n-heptane) was first added to the reactor in an amount equal to the amount of the bifunctional catalyst. The resulting polymer was named PE-Ni1 / BHT.
[0117] Example 5: Natural Antioxidant Carrier Enhancement Strategy
[0118] Natural antioxidant carriers such as leucine and tannic acid were treated with triisobutylaluminum (1.1M hexane solution, 1.0 eq.) dropwise under nitrogen atmosphere. After stirring for 1 h, the mixture was filtered, washed with n-hexane, and dried under vacuum to obtain pretreated natural antioxidant carriers.
[0119] Polyolefin materials were prepared using the same method as in Example 1, except that: phosphonol ligands and an equimolar amount of Ni(COD)₂ were dissolved in n-heptane to form a Ni₂ catalyst, and 1.2 equivalents of sodium hydride (NaH) were added simultaneously. The mixture was stirred for 30 min to obtain a sodium phenolate-functionalized Ni₂ catalyst. The pretreated natural antioxidant support was added to the sodium phenolate-functionalized Ni₂ catalyst to achieve a metal loading of 100 µmol / g. After adsorption by stirring, the catalyst was washed with n-heptane until the filtrate was colorless, vacuum dried, and resuspended in n-heptane to form a heterogeneous catalyst. The aforementioned heterogeneous catalyst was used to catalyze the polymerization of ethylene monomers. In this case, 5 mg of the heterogeneous catalyst (containing approximately 0.5 μmol Ni) was used instead of the homogeneous catalyst in Example 1, while the other reaction conditions remained the same. The resulting polymers were named PE-Ni₂ / white lignin and PE-Ni / tannic acid, respectively.
[0120] Comparative Example 1
[0121] UHMWPE control samples with different antioxidant contents were prepared according to the commonly used industrial solution impregnation method (refer to US10265891 B2, EP 1161489 B1). Specifically, a certain amount of vitamin E or antioxidant 1010 (Irganox 1010) was dissolved in isopropanol, and then commercial UHMWPE powder (GUR 1050) was added. After physical mixing and stirring for 6 hours, the mixture was dried under vacuum at 60°C for 3 days to obtain UHMWPE blend powders with antioxidant contents of 0.015 wt%, 0.03 wt%, 0.15 wt%, and 0.3 wt%, respectively.
[0122] Polyolefin materials were prepared by catalytic polymerization of ethylene using the bifunctional catalysts described in Examples 1-5 above. The prepared polyolefin materials included branched polyethylene, polyethylene wax, bimodal polyethylene, and UHMWPE powder. The molecular weight, catalytic activity, and typical mechanical properties of the obtained polymers are shown in Table 1.
[0123] Table 1
[0124]
[0125] All activities (Act., 10) 6 g·mol -1 ·h -1 The weight-average molecular weight (M) is calculated from the average mass of the polymer obtained through polymerization. w 10 4 g·mol -1 PDI and PDI were determined by gel permeation chromatography. Stress / strain tests were performed at room temperature at a rate of 10 mm / min, with at least three specimens tested for each polymer. Each polymer was melt-pressed at approximately 180°C and 5 MPa for 5 minutes to obtain specimens. The dumbbell-shaped specimens had the following dimensions: gauge length 28 mm; width 2 mm; thickness approximately 0.5 mm.
[0126] The UHMWPE powder prepared using Ni1, Ni2, and Ni3 catalysts in Example 1 above was compared with the thermal properties, oxidation induction time (OIT), and initial oxidation temperature (Td0) of the commercial UHMWPE control sample prepared using different amounts of microbial E in Comparative Example 1. Specific test results are as follows: Figures 2-3 As shown.
[0127] Figure 2 This is a graph showing the oxidation induction time of different samples in Example 1 of the present invention. Figure 3 This is a diagram showing the initial oxidation temperature of different samples in Example 1 of the present invention.
[0128] like Figures 2-3 As shown, the PE-Ni3 sample exhibits an OIT (Oil Intake) of up to 45 min and a Td0 of up to 245 °C, which not only far exceeds that of commercially available ultra-high molecular weight polyethylene (UHMWPE) without antioxidants, but also surpasses the vitamin E-impregnated sample with a content as high as 0.3 wt% (OIT approximately 30 min). Furthermore, combining the mechanical property data in Table 1, the PE-Ni3 sample demonstrates a tensile strength of up to 61 MPa and an elongation at break of approximately 210%, meeting application requirements.
[0129] The residual amount of metallic Ni in commercial ultra-high molecular weight polyethylene and PE-Ni3 was analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES). The specific test results are shown in Table 2 below.
[0130] Table 2
[0131]
[0132] ND means not detected
[0133] As shown in Table 2, ICP-OES analysis showed that the residual nickel content in PE-Ni3 was 18.77 mg / kg (approximately 0.0019 wt%), which translates to a ligand content of approximately 0.015 wt%, indicating that high-efficiency oxidation resistance was achieved with a relatively low content of bifunctional catalyst (i.e., antioxidant structure).
[0134] In Example 2 above, Ni, Ni4-OH, Ni5, Ni5-OH, Fe-OH, Ti-OH and other catalysts were used to polymerize ethylene to prepare polyolefin materials. The prepared polyolefin materials include branched polyethylene, polyethylene wax, bimodal polyethylene and UHMWPE. The mechanical properties of different polymers are shown in Table 1.
[0135] Figure 4 This is the NMR spectrum of the polymer PE-Ni4 sample in Example 2 of this invention. Figure 5 This is the NMR spectrum of the polymer PE-Ni4-OH sample in Example 2 of the present invention; Figure 6 This is a graph showing the oxidation induction time of different samples in Example 2 of the present invention.
[0136] Taking the α-diimine nickel system as an example, after introducing phenolic hydroxyl groups, the degree of branching of the polymer decreased from 84 / 1000C to 25 / 1000C. Figure 4 and 5 ), with molecular weights ranging from 2.2 × 10⁻⁶ 5 Increased to 8.0×10 5 g / mol, the tensile strength jumped from 2.4 MPa to 35.5 MPa, and the OIT was greatly improved (e.g. Figure 6 In titanium-based and iron-based catalysts, the introduction of phenolic hydroxyl groups significantly improves the OIT (Original Inertia) of the polymer (e.g., ...). Figure 6 Meanwhile, the tensile strength of UHMWPE remained at 60 MPa. These results indicate that bifunctional catalysts formed by introducing hydroxyl groups onto the aromatic ring can effectively impart intrinsic antioxidant functions to polyolefins with different structures without sacrificing or even improving mechanical properties, compared to catalysts without introducing hydroxyl groups onto the aromatic ring. Furthermore, they can improve the microstructure of the polymer (such as reducing branching, increasing molecular weight and tensile strength).
[0137] Figure 7 This is a comparison chart of oxidation induction times for samples prepared with the introduction of auxiliary antioxidants in Example 4 of the present invention. Figure 8 This is a diagram showing the initial oxidation temperature of the sample prepared by introducing an auxiliary antioxidant in Example 4 of the present invention.
[0138] like Figures 7-8As shown, during the olefin polymerization process, adding an amount of BHT auxiliary antioxidant equal to that of the Ni catalyst significantly increased the oxidation induction time (OIT) of the PE-Ni1 / BHT sample from 13 min to 45 min, and the initial oxidation temperature (Td0) from 215℃ to 255℃ compared to the PE-Ni sample.
[0139] Figure 9 This is a comparison chart of oxidation induction times for samples prepared by introducing a natural antioxidant carrier in Example 5 of the present invention. Figure 10 This is a diagram showing the initial oxidation temperature of the sample prepared by introducing a natural antioxidant carrier in Example 5 of the present invention.
[0140] As shown in Table 1, the tensile strength of PE-Ni2 / white lignin reaches 61 MPa, which is 33% higher than that of the unloaded natural antioxidant carrier system. Furthermore, combined with... Figures 9-10 As shown, Ni2 catalyst was supported on natural antioxidant supports such as leucine and EGCG to synthesize ultra-high molecular weight polyethylene. OIT test results showed that all the supported natural antioxidant support systems had better antioxidant performance than the pure Ni2 system. Among them, PE-Ni2 / T tannic acid had an OIT of up to 67 min and a Td0 of 267℃.
[0141] Example 6
[0142] The PE-Ni3 sample and the control sample (commercial UHMWPE containing 0.015 wt% vitamin E) were hot-pressed into sheets, then packaged and... 60 The radiation-crosslinked polyolefin materials obtained by irradiating Co gamma rays with 50 kGy (dose rate 35.92 Gy / min) were named C-commercial ultra-high molecular weight polyethylene (UHMWPE) (0.015wt%) and C-PE-Ni3, respectively.
[0143] Figure 11 These are the electron spin resonance (ESR) spectra of different samples after radiation crosslinking in Example 6 of this invention. Figure 12 This is a graph showing the oxidation induction time of different samples before and after radiation crosslinking in Example 6 of the present invention. Figure 13 This is a graph showing the anti-creep properties of different samples before and after radiation crosslinking in Example 6 of the present invention.
[0144] like Figure 11 As shown, ESR analysis of the unannealed C-PE-Ni3 sample after irradiation revealed a significantly lower free radical concentration than the control sample C-commercial ultra-high molecular weight polyethylene (0.015 wt%), indicating that most free radicals were efficiently scavenged during irradiation. Figure 12As shown, although the oxidation induction time of the C-PE-Ni3 sample decreased somewhat after irradiation and vacuum annealing at 120℃, it was still much longer than that of the control sample C-commercial ultra-high molecular weight polyethylene (0.015wt%) treated with the same method. Regarding mechanical properties, such as... Figure 13 The cross-linked C-PE-Ni3 sample showed a 73% retention rate of elongation at break, compared to only 39% for the control sample; the permanent creep elongation was only 5.5%, demonstrating excellent creep resistance. These indicators suggest that the intrinsically antioxidant UHMWPE of this invention is highly suitable for radiation-cross-linked implants such as artificial joints.
[0145] Example 7
[0146] Gel spinning was performed using the PE-Ni3 sample from Example 1 and the PE-Ni2 / white lignin sample from Example 5. Specifically, the polymer was dissolved in white oil at a concentration of 3 wt%, cooled, and extruded through a 0.5 mm spinneret at 150 °C. The polymer was then ultrasonically extracted three times with dichloromethane, dried, and subjected to three stages of hot stretching at 90 °C (stretch ratios of 10, 2, and 1.5).
[0147] Figure 14 The graph shows the mechanical properties of different fiber samples in Example 7 of this invention. Figure 15 The graphs show the mechanical properties of different fiber samples after different aging times in Example 7 of this invention.
[0148] like Figures 14-15 As shown, the monofilament strength of both PE-Ni3 and PE-Ni2 / white lignin fibers exceeds 40 cN / dtex, and the initial modulus is higher than 1000 cN / dtex. Control fibers containing an equal amount of vitamin E (0.015 wt%) were compared with those of PE-Ni3 and PE-Ni2 / white lignin fibers in an air oven at 100℃ after 168 hours of testing. PE-Ni3 fiber showed a strength loss of only 17%, while the control fiber (UHMWPE 0.015 wt%) showed a strength loss as high as 35%, fully demonstrating the long-term thermal stability advantage of intrinsically antioxidant fibers.
[0149] In summary, this invention utilizes transition metal complexes containing phenolic hydroxyl groups as bifunctional catalysts. These catalysts catalyze olefin polymerization without the need for external antioxidants, imparting antioxidant properties to polyolefins through the residual bifunctional catalyst. This method is applicable to various polyolefin types, particularly ultra-high molecular weight polyethylene (UHMWPE). Furthermore, the antioxidant effect can be further enhanced by adding auxiliary antioxidants in combination with the bifunctional catalyst, or by using natural antioxidant supports to load the bifunctional catalyst. The polyolefin materials prepared using this method exhibit low residual amounts of the bifunctional catalyst (i.e., the antioxidant structure) (at the ppm level), significantly improved oxidation induction time and initial oxidation temperature, while maintaining excellent mechanical properties. Based on this material, radiation-crosslinked polyolefin materials, high-strength and high-modulus fibers, etc., can be prepared, showing broad application prospects in medical implants, protective materials, and other fields.
[0150] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a polyolefin material with intrinsic antioxidant properties, characterized in that, include: In a polymerization solvent, a bifunctional catalyst is used to catalyze the polymerization reaction of at least one olefin monomer to obtain a polyolefin material with intrinsic antioxidant properties. The bifunctional catalyst is a transition metal complex containing phenolic hydroxyl groups, wherein the phenolic hydroxyl groups are located on the backbone or side chain of a ligand coordinated with the center of the transition metal, or are directly coordinated with the center of the transition metal.
2. The preparation method according to claim 1, characterized in that, The ligand is selected from any one of phosphonophenol ligand, α-diimine ligand, pyridine-imine ligand, pyridine-bisimine ligand, and bis(phenoxy-imine) ligand; The transition metal is selected from any one of Group IVB, Group VB, Group VIB, Group VIIB, Group VIII, Group IB or Group IIB metals; Preferably, the ortho and / or para positions of the phenolic hydroxyl group are substituted with at least one substituent selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, hydroxyl, alkoxy, aryloxy, aralkyloxy, oxo (carbonyl), carboxyl, carboxylate, carboxylate ester, mercapto, alkylthio, arylthio, sulfoxide, sulfonyl, sulfonamide, amino, hydroxyamino, nitrile, nitro, cyano, acylhydrazine, azide, and enamine; More preferably, the substituent is selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydroxyl, and carboxyl groups; Preferably, the transition metal is selected from at least one of titanium, zirconium, hafnium, vanadium, chromium, iron, cobalt, nickel, and palladium.
3. The preparation method according to claim 2, characterized in that, Also includes: Adding an auxiliary antioxidant creates a synergistic antioxidant effect with the bifunctional catalyst. The auxiliary antioxidant is selected from at least one of butylated hydroxytoluene and tert-butylhydroquinone; The amount of the auxiliary antioxidant is 0.1 to 10 times the molar amount of the bifunctional catalyst.
4. The preparation method according to claim 2, characterized in that, Also includes: The bifunctional catalyst is loaded onto a natural antioxidant support to form a heterogeneous catalyst that catalyzes the polymerization reaction of at least one olefin monomer. The natural antioxidant carrier is selected from at least one of lignin, leucine, epigallocatechin gallate, tannin, carotenoids, terpenoids, and vitamins.
5. The preparation method according to claim 2, characterized in that, The bifunctional catalyst has any of the following structures: Equation (1) Equation (2), Equation (3) Equation (4) Equation (5); Among them, R1, R2, and R3 are each independently selected from C1-C 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydrogen, and hydroxyl groups, where Ar1 and Ar2 are each independently selected from substituted or unsubstituted C6-C groups. 20 Aryl or C4-C 20 Heteroaryl groups, in which the heteroatom can be any one of N, S, or O, and the substituents are selected from C1-C1. 10 Alkyl, C1-C 10 Alkoxy, C6-C 20 At least one of aryl, halogen, nitro, cyano, hydroxyl, and carboxyl groups; M is a transition metal; X1 and X2 may be the same or different, and each is independently selected from Br and Cl.
6. The preparation method according to any one of claims 1-5, characterized in that, The polymerization solvent is selected from any one of hexaane, n-heptane, cyclohexane, and toluene; The polymerization reaction is precipitation polymerization, which allows the bifunctional catalyst to be embedded in situ into the polyolefin material, achieving uniform dispersion.
7. A polyolefin material prepared by the method according to any one of claims 1-6, characterized in that, The residual amount of the bifunctional catalyst in the polyolefin material is 0.005wt%-0.5wt%.
8. The polyolefin material according to claim 7, characterized in that, The polyolefin material includes at least one of branched polyethylene, polyethylene wax, bimodal polyethylene, and ultra-high molecular weight polyethylene; Preferably, when the polyolefin material is ultra-high molecular weight polyethylene, the weight-average molecular weight is 1×10⁻⁶. 6 ~ 2×10 7 g / mol, tensile strength of 40MPa-70MPa, and elongation at break of 150%-600%; Preferably, the oxidation induction time of the polyolefin material at 200°C in a pure oxygen atmosphere is 5-60 min.
9. A polyolefin material product, characterized in that, The polyolefin material products include radiation-crosslinked polyolefin materials or polyolefin fibers; The radiation-crosslinked polyolefin material is obtained by irradiation crosslinking treatment of the polyolefin material according to any one of claims 7-8; Preferably, the irradiation crosslinking is performed using gamma rays or an electron beam, with a total dose of 10 kGy to 200 kGy; The polyolefin fiber is obtained from the polyolefin material according to any one of claims 7-8 by gel spinning and multi-stage thermal stretching; Preferably, the polyolefin fiber has a monofilament tensile strength ≥40 cN / dtex and an initial modulus ≥1000 cN / dtex.
10. The application of the polyolefin material as described in any one of claims 7-8, or the polyolefin material article as described in claim 9, in textiles and medical devices.
Citation Information
Patent Citations
A method for the preparation of uhmwpe doped with an antioxidant and an implant made thereof
EP1161489B1
Antioxidant-infused ultra high molecular weight polyethylene
US10265891B2